Causal links between blood inflammation markers and postherpetic neuralgia risk: insights from a two-sample Mendelian randomization study - Wang, Yu; Jia, Tian (Frontiers in Neurology, 2024)
Introduction Previous studies have suggested an association between blood inflammation-related factors and postherpetic neuralgia. However, the causal relationship between blood inflammation-related factors and postherpetic neuralgia remains unclear. Methods We employed a bidirectional Two-sample Mendelian randomization (MR) analysis to explore the causal relationship between blood inflammation-related factors and postherpetic neuralgia. The instrumental variables were obtained from a large Genome-wide association study (GWAS) meta-analysis dataset of European descent. The instrumental variables of the blood inflammation-related factors come from the database numbers GCST004420 to GCST004460 and GCST90029070. Postherpetic neuralgia has 195,191 samples with a total of 16,380,406 single nucleotide polymorphisms (SNPs). MR analyses were performed using inverse-variance weighted, MR-Egger, and weighted median methods. Results The MR results revealed a significant causal effect of Macrophage Inflammatory Protein 1 Beta (MIP1β) on reducing the risk of postherpetic neuralgia (95%CI = 0.492–0.991, p = 0.044). Additionally, higher levels of interleukin (IL)-10 (95%CI = 0.973–0.998, p = 0.019) and IL-12p70 (95%CI = 0.973–0.997, p = 0.013) were associated with a lower risk of postherpetic neuralgia. Other inflammatory markers showed no significant causal relationship with this condition. Conclusion This study identifies MIP1β, IL-10, and IL-12p70 as potential therapeutic targets for preventing or treating postherpetic neuralgia, underscoring the need for further research in this area.